Life Cycle Cost Evaluation For Enhancing Design For Reuse (Jurnal Inovisi (Teknik Industri), 2011)
AbstractProduct recovery strategies such as reuse, remanufacture and recycling requires a cost analysis that covers the entire product life cycle, from the design concept to the recovery and disposal.  Life cycle cost estimation provides a framework for identifying the best design alternatives that can satisfy both economics and environmental requirements.   This paper presents a life cycle cost analysis (LCCA) on a locally manufactured car door with the aim of enhancing the reusability of the car door.  The existing design of the car door was evaluated and some design modifications for ease of disassembly are proposed in view of enhancing reusability and cost. Significant improvements to the design of the car door that satisfy the disassembly and life cycle cost are presented and discussed in this paper.Keywords: design for reuse, life cycle cost analysis, disassembly